2016
DOI: 10.4018/ij3dim.2016010105
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Information Retrieval (3DIR)

Abstract: An increasing amount of information is packed into BIMs, with the 3D geometry serving as a central index leading to other information. The 3DIR project investigates information retrieval from such environments. Here, the 3D visualization can be exploited when formulating queries, computing the relevance of information items, or visualizing search results. The need for such a system was specified using workshops with end users. A prototype was built on a commercial BIM platform. Following an evaluation, the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For example, Hua (2014) developed a commercial CBR software: TRAMMA programme, which is capable of storing and retrieving the 3D models of buildings to facilitate CBR use along with BIM during building design. Demian et al (2016) investigated specific topological relationships which exist in BIM models and how they can be exploited usefully for information retrieval. Furthermore, Sönmez (2018) suggested that novel AI techniques and similarity-based evaluation may contribute to advancements of CBD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Hua (2014) developed a commercial CBR software: TRAMMA programme, which is capable of storing and retrieving the 3D models of buildings to facilitate CBR use along with BIM during building design. Demian et al (2016) investigated specific topological relationships which exist in BIM models and how they can be exploited usefully for information retrieval. Furthermore, Sönmez (2018) suggested that novel AI techniques and similarity-based evaluation may contribute to advancements of CBD.…”
Section: Literature Reviewmentioning
confidence: 99%